EVALUATION OF THE ANALYTICAL CAPABILITY OF THERMAL DESORPTION ATOMIC ABSORPTION SPECTROMETRY METHOD USED FOR MERCURY DETERMINATION IN SEAFOOD - SENILA, Marin; CADAR, Oana; DROLC, Andreja; PINTAR, Albin; SENILA, Lacrimioara; FRENŢIU, Tiberiu (Studia Universitatis Babeș-Bolyai Chemia, 2016)
Mercury is recognized as a highly toxic and widespread element in environment that can be transferred in the whole food chain. Thus, the content of mercury in foodstuff become of great interest. The aim of this paper is to assess the analytical capability and validation of the method for quantitative determination of total mercury (Hg) in seafood using thermal desorption atomic absorption spectrometry (TD-AAS). TD-AAS is a simple technique which does not require sample digestion prior to analysis. The main figures of merit such as selectivity, linearity, limit of detection (LoD), limit of quantification (LoQ), working range, accuracy and precision were studied and discussed in relation with the requirements in the Commission Decision 2002/657/EC and Commission Regulations 2011/836/EU and 2007/333/EC. Measurement uncertainty was estimated using top-down approach and was compared with the maximum uncertainty value calculated as specified in the Commission Decision 2002/ 657/EC. LoD estimated using 3s criterion was found to be 3.0 µg kg-1, while LOQ 9.0 µg kg-1. The recovery (%), estimated by using the certified reference material BCR-463 Tuna Fish, was 95 ± 5.0 %, whereas recovery (%) estimated using spiked samples was 92 ± 5.6 %. Standard deviation of repeatability (sr) was 5.6% (n=10 parallel samples), while standard deviation of within-laboratory reproducibility (sR) was 9.8 % (n=10 parallel samples), which correspond to HorRat’s index for repeatability and reproducibility of 0.28 and 0.50, respectively. The estimated expanded relative uncertainty (k=2) was 15.6 %. The obtained figures of merit fulfil the requirements of the European legislation and demonstrate that the laboratory can properly apply the method in order to achieve accurate results. The paper represents a model for the method validation in analytical laboratories in order to check the fit for purpose of analytical methods.